Perception of local communities towards the potential of bird watching activity as ecotourism product in Rompin - Mohamed Zakaria, Hasan (2016)
An ecotourism product must involve the element of local community as part of the product. Large biodiversity in Menchali Forest Reserve Rompin create a big potential for bird watching activity to be done as an ecotourism product. The main objective of this study is to evaluate the perception of local communities towards the potential of bird watching activity in Rompin as ecotourism product. Non-parametric test and ANOVA were used to identify the difference between local community’s socio-demographic variables towards bird watching activity. Five factors were found to be significant at 95% confidence level which affected the perception towards bird watching activity mainly age, ethnic, level of education, monthly income and housing area. Positive perception was shown by the local communities for all aspect but slightly difference in mean for each aspect that have significant value. Hence, it can be concluded that perception towards bird watching activities is affected by the age, ethnic, level of education, monthly income and housing area. These findings may be providing knowledge for ADUN, City Council and local community to develop bird watching activity in Rompin.